Konsep Harta dalam Akuntansi Syariah: Integrasi Nilai Kepemilikan dan Tanggung Jawab Sosial di Indonesia - Khatimah, Husnul; Awalyah Gusdayanti; Masyhuri (Journal of Islamic Economic Studies, 2025)
The concept of wealth in sharia accounting not only emphasizes individual ownership but also highlights its social function to achieve justice and collective welfare. Wealth is viewed as a trust (amanah) from Allah SWT, and its utilization is directed through instruments such as zakat, infaq, sadaqah, and waqf. This study aims to examine the integration of ownership values and social responsibility in sharia accounting reporting, as well as to analyze the challenges of its implementation in Indonesia. The methodology employed is a qualitative-descriptive approach, utilizing a literature review of academic works, sharia accounting regulations, and financial reporting documents from Islamic institutions. The findings indicate that sharia accounting plays a significant role in realizing fair, transparent, and accountable wealth reporting. However, its implementation still faces obstacles such as low financial literacy, diverse understandings of the concept of wealth, and limitations in social fund reporting systems. Collaboration between regulators, sharia institutions, and the community is needed to strengthen a sharia-based reporting system that supports the realization of social justice in Indonesia.